PRODUK DOMESTIK REGIONAL BRUTO (PDRB) HIJAU SEKTOR PERTANIAN DI KABUPATEN JAYAPURA - Lestari Rahayu Waluyati; Any Suryantini; Herman Masbaitubun (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2010)
Gaps in the farming development have caused the damage to land because of erosion and sedimentation. Utilization of and on the river outskirts and a steep hill without conservation principle, has led to soil damage that is difficult to be restored again. The use of production facilities in the form of chemicals such as fertilizers, pest, diseases and weeds eradications, in the form of pesticides, insecticides, fungicides, and herbicides are not appropriate, cause adverse side effect to the crops, farmers and environment. Similarly, use of eradications that pollute the waters around the plantation and it is harmful to humans, fish and livestock. Admission of environmental dimension, such as natural resources depletion and environmental degradation, in conventional GDP calculation requires modeling of Green GDP. In the modeling of Green GDP, natural resources depletion and degradation are subjects of numerous recounts. Time series data of 2006-2008 were used in analysis. Accroding to conventional GDP calculation from 2006-2008, there was declination of agricultural sector’s contribution in GDP . agricultural sector’s contribution in Jayapura regency based on 2006 was up to 40,16 percent, 37,97 ercent in 2007, and 35,8 percent in 2008. The degradation value of natural resources were much greater than their depletion value. However according to Green GDP calculation, agricultural sector’s contribution of 2006-2008 in Jayapura regency were in state of inclination. Based on GDP data of Jayapura regency, in 2006 the contribution inclined up to 181.791,46 milion Rupiah (45,43 percent), 153.495,13 milion Rupiah (34,98 percent) in 2007, and 176.664,89 milion Rupiah (36,96%) in 2008. Commitment to admit environmental dimensions as an important aspect in developmental planning is key to succesfull model of Green GDP and environmental plicy in general. DAS conservation, reforestation, and activism of those kind need to be promoted in order to reduce environmental degradation.